2009
DOI: 10.1371/journal.pone.0005375
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of Clinical Information in the Histopathologic Diagnosis of Melanocytic Skin Neoplasms

Abstract: BackgroundWe tested the relevance of clinical information in the histopathologic evaluation of melanocytic skin neoplasm (MSN).MethodsHistopathologic specimens from 99 clinically atypical MSN were circulated among ten histopathologists; each case had clinical information available in a database with a five-step procedure (no information; age/sex/location; clinical diagnosis; clinical image; dermoscopic image); each step had a histopathologic diagnosis (D1 through D5); each diagnostic step had a level of diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 28 publications
4
67
1
Order By: Relevance
“…It has previously been shown that clinical and dermatoscopic data can enhance histopathologic diagnosis of melanoma among pathologists. 10,19 Our series support the use of a combined diagnostic method approach for pigmented lesions to enhance detection of early melanoma. 11,20 In the past decade targeted molecular techniques have become available to further assist in the diagnosis of histologically challenging melanocytic neoplasms.…”
Section: Discussionsupporting
confidence: 53%
“…It has previously been shown that clinical and dermatoscopic data can enhance histopathologic diagnosis of melanoma among pathologists. 10,19 Our series support the use of a combined diagnostic method approach for pigmented lesions to enhance detection of early melanoma. 11,20 In the past decade targeted molecular techniques have become available to further assist in the diagnosis of histologically challenging melanocytic neoplasms.…”
Section: Discussionsupporting
confidence: 53%
“…The need for appropriate clinical correlation and clinical images has already been underlined. 8,9 Recently, the usefulness of clinicopathologic correlation for the histopathologic diagnosis of melanocytic skin tumor was demonstrated, 3,6 and it was suggested that all biopsy specimens of clinically difficult pigmented lesions should be assessed histopathologically with knowledge of the clinical picture. 10 In this context, we stress that dermatopathology is macroscopic and microscopic pathology of the skin, and that evaluation of clinical presentation (macroscopy) represents a crucial step in the diagnostic process.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly for pigmented skin tumors, the feasibility of teledermatology has been successfully evaluated in several studies, even with the use of cellular phoneebased cameras. [2][3][4][5][6] The current study was performed to verify whether the evaluation of clinical pictures increases the accuracy of dermatopathologic diagnosis of inflammatory skin disorders.…”
Section: Introductionmentioning
confidence: 99%
“…19 Our research group 20 has suggested a technique whereby the clinician sends a dermoscopic image of the lesion to the pathologist, who then uses the image during gross examination as a tool to identify the dermoscopically suspect areas that are annotated on the image. 20 In addition, step sectioning of melanocytic lesions decreases the chance of sampling errors.…”
Section: Decreasing the Rate Of Misdiagnosismentioning
confidence: 99%